2021
DOI: 10.3390/app11114854
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Quality Management System on the Operation of Periodical Technical Inspection Stations

Abstract: This article deals with the minimum requirements for quality management at Periodical Technical Inspection Stations (PTIS) for road vehicles in the Slovak Republic, as well as in selected countries of the European Union. Specifically, it contains research performed at all of the PTIS in the Slovak Republic with a focus on the established quality management system and the number of employees of companies operating these PTIS, as well as similar research in selected countries of the European Union. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…On average, traffic accidents were occurring in this category no more than half a year before the end of the validity of the periodic technical inspection. It follows from the above that with the approaching end of the period of validity of periodic technical inspection, the occurrence Therefore, instead of calling the systems of periodic technical inspections into question, national authorities should rather take more stringent measures to improve the performance of PTI (especially at the EU level), such as the introduction at PTI of compulsory accreditation under ISO 17020 [41], which has a demonstrably positive effect on the quality of the PTI activity [42], as well as pay attention to inspections of PTI. As an example may serve the Slovak Republic, where inspection bodies effectively control the activities of technicians through cameras, thanks to which, after the introduction of this control system, the rate of temporary roadworthiness and non-worthiness in the assessment of vehicles at PTIs increased significantly and, in correlation with this, decreased the number of traffic accidents due to vehicle technical defects.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…On average, traffic accidents were occurring in this category no more than half a year before the end of the validity of the periodic technical inspection. It follows from the above that with the approaching end of the period of validity of periodic technical inspection, the occurrence Therefore, instead of calling the systems of periodic technical inspections into question, national authorities should rather take more stringent measures to improve the performance of PTI (especially at the EU level), such as the introduction at PTI of compulsory accreditation under ISO 17020 [41], which has a demonstrably positive effect on the quality of the PTI activity [42], as well as pay attention to inspections of PTI. As an example may serve the Slovak Republic, where inspection bodies effectively control the activities of technicians through cameras, thanks to which, after the introduction of this control system, the rate of temporary roadworthiness and non-worthiness in the assessment of vehicles at PTIs increased significantly and, in correlation with this, decreased the number of traffic accidents due to vehicle technical defects.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Better production and possession of the certificate should lead to higher sales, which will also be reflected positively in the financial perspective, which will be measured by the return on assets (ROA) indicator. From this, it can be concluded that a company that decided to make a strategic decision and implemented a quality management system according to the ISO 9001 standard should achieve better financial results than in the years when it did not have the standard through internal and external benefits obtained, or through both benefits at the same time [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The heightened monitoring has resulted in a higher failure rate during PTI inspections, which increased from 6.2% to 13.1% in March 2019, more than doubling the failure rate; the trend in failure rate from 2013 to 2021 is shown in Figure 1. A comprehensive summary of the quality management and assessment of PTI stations in Slovakia and other selected EU countries is presented in [42]. The implementation of a mobile application has been enhancing the supervision of technical vehicle inspection (PTI) in Slovakia since 1 January 2020.…”
Section: Pti In Slovak Republicmentioning
confidence: 99%